A microbiota-derived antigen drives CD4+ intraepithelial lymphocyte (CD4IEL) development. Issue 11 (November 2022) - Cervantes-Barragan, Luisa; Colonna, Marco
Abstract: CD4 + intraepithelial lymphocytes (CD4IEL) are tissue-resident T cells with cytotoxic and regulatory properties; together with peripheral regulatory T cells, they control intestinal inflammation. Recently, Bousbaine and colleagues identified a microbiota-derived conserved antigen that induces CD4IEL differentiation and promotes their regulatory function, attenuating the severity of murine colitis.